Estratigrafia dos grupos Canastra e Ibiá (Faixa Brasília Meridional) na região de Ibiá, Minas Gerais: caracterização e estudo de proveniência sedimentar com base em estudos isótopos U-Pb e Sm- Nd - Paulo Henrique Amorim Dias (2011)
The Southern Brasília Belt (SBB) represents the southeastern branch of the Tocantins Province, which also includes intra-oceanic magmatic arcs and ophiolites. Nappe systems characterize the SBB and show tectonicaly stacked packages dominated by siliciclastic rocks. This dissertation focuses on the Araxá nappe and related stratigraphic units called, from west to east, Araxá, Ibiá and Canastra groups. The youngest magmatic rocks are granitoids dated from 640 Ma to 620 Ma. Systematic field studies show that a matrix-supported metaconglomerate with intercalations of quartz metapelite and quartzite (Cubatão Formation) form sparse lenses that overlie local erosional unconformities on the top of the metapelite-quartzite succession of the Canastra Group. Most clasts of this conglomerate are pebbles to boulders of quartzite and quartz that could be provided by the Canastra Group. In fact, U-Pb ages of detrital zircon grains from the Cubatão conglomerate and Canastra quartzite show similar large age spectra and, in both cases, the grains are well-rounded and the youngest zircons have ages around 1000 Ma. The Cubatão Formation lenses, as well as the Canastra Group, show sharp contacts with the overlying Rio Verde Formation (Ibiá Group). This formation consists of an extensive package of laminated chlorite-muscovite metapelite with variable quartz and carbonate contents, and a few quartzite lenses to the top. Contrasting to both the Canastra Group and Cubatão Formation, U-Pb data from detrital zircon grains of the Rio Verde schist show a bimodal age spectra, with most values ranging from 640 Ma to 1050 Ma, and a minor group from 1800 Ma to 2200 Ma. The youngest group of grains often show poorly rounded to euhedral zircon crystals, some of them of volcanic origin. On the contrary, the oldest group of grains shows well-rounded shapes, akin to those of the Canastra and Cubatão samples. The Sm-Nd isotopic data for the Rio Verde metapelite yielded TDM model ages around 1.2 Ga and negative to slightly positive epsilon Nd(640 Ma) values. The analytical data together with the composition of the Rio Verde metapelite (rich in muscovite and chlorite) suggest provenance from sources rich in pelitic rocks and mafic to intermediate igneous (volcanic) rocks, like the Araxá Group, ophiolites and magmatic arcs. However, the youngest zircons (ca. 640 Ma) suggest contribution from the collisional granites, so that the Rio Verde Formation can be related to a collisional flysch-type basin associated with thrust fronts. In this scenario, the timing from sedimentation to tectonic inversion in the Rio Verde basin would be relatively short, between ca. 640 Ma (age of the youngest detrital zircons) to 620 Ma (age of the youngest collisional granitoids). On the other hand, the Canastra Group records Tonian shelf sedimentation along the western passive margin of the São Francisco paleocontinent. Although no solid evidence of glaciation has ever been found in the Cubatão Formation, it may record a Neoproterozoic glacial event younger than ca. 1000 Ma. Alternatively, this formation could represent fanglomerate deposits formed by local erosion, mainly of the Canastra Group, along thrust fronts and subsequently covered by the Rio Verde flysch.